STRATEGI PEMBANGUNAN INFRASTRUKTUR JALAN DI KOTA DUMAI - Syafitri, Nurul Serlyan; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The construction of road infrastructure in Dumai City is an important basic infrastructure to improve considering the city of Dumai has strategic value as the gateway to the coast of Sumatra, and is supported by the vision and mission of Dumai City. Quality Improvement & Quantity of road Infrastructure development aims to optimize services to the community as well as to encourage the development of Dumai City in accordance with the City Strategic Plan going forward taking into account the impact as a result of considerable City changes. But in reality the construction of road infrastructure in Dumai City has not been done optimally, this is due to several factors found in the field. This research aims to find out the strategy of road infrastructure development in Dumai City and the inhibitory factor of road infrastructure development in Dumai City. This research uses qualitative methods with a descriptive case study approach. Informants are taken using purposive sampling. Data collection is done with observations, interviews, and documentation later in the analysis based on the formulation of research problems. The results of this study show that the construction of road infrastructure in Dumai City has not been done optimally, based on the selection of technology used, determination of authority, coordination, embodiment, and system management. The inhibitory factor in the construction of road infrastructure in Dumai City is the natural condition factor and the leader's policy factor. So that the PUPR Office or the relevant government can increase information openness through open access, in addition it needs to be improved the quality of coordination meetings when determining priority roads so that what has been set does not need to be re-enacted due to the policy of the leader.Keywords: Strategy, Development, Road Infrastructure, Dumai City